PKM SOSIALISASI HIDUP SEHAT TANPA ROKOK PADA REMAJA SEKOLAH - Farkhahi Farkhahi (Jurnal Pengabdian Ilmu Kesehatan, 2021)
The cycle of cigarettes is increasingly widespread because people, especially teenagers, think that cigarettes are a symbol of association and maturity. Sometimes we often hear words from teenage smokers saying that they will not be accepted in their social environment if they do not smoke. Currently, cigarette products have spread throughout the world with an increasing number of consumers. This service activity is expected to be a source of motivation for the community in general and teenagers in particular. This is important because by increasing their understanding and perception, it is hoped that it will prevent teenagers from becoming novice smokers or wanting to quit for those who are currently doing it. So that health education like this should be sustainable because the perception of teenagers will quickly change again by having a healthy lifestyle without smoking.